(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
Objective: To evaluate the outcome of chronic Monteggia fracture treated with ulna lengthening and angulation with or without open reduction of radial head. Methodology: A descriptive study comprising of total 11 cases were included in this study presented to Hayatabad medical complex Peshawar from January 2020 to june 2021. Patients presented with chronic monteggia fracture after 4 weeks of injury were included in the study. All the cases were done by same surgeon in same setup and environment by lengthening and angulation of ulna with z osteotomy and plating with and without open reduction of radial head. Patients were evaluated at 2 weeks, 6 weeks, 3 months, 06 months and 1 year follow ups. Result: Out of 11 cases 63.63% (n=07) were boys and 36.36% (n= 04) were girls. Mean age of 07±2.32 years (range, 04 to 11 years). The mean duration of time between initial injury and presentation is 12.3 ± 6.3 weeks (range, 4 weeks to 24 weeks). Radial head reduction was achieved in all cases by doing ulnar lengthening and angulation with z osteotomy and plating including 03 cases which needed further open reduction and annular ligament reconstruction for radial head reduction. On follow ups out of 11, 10 patients had excellent range of movement and good functional outcomes while, 01 case had sublaxated radial head. Conclusion: Lengthening and angulation of ulna with z osteotomy and plating is best procedure for chronic Monteggia fracture, with low complication rate and excellent functional outcome.